A Project Report on Multi Protocol Mail Server - KUMAR VISHA, DAVID CARVALHO and MAYUKH BISWAS (2008)
INTERNAL GUIDE: GAYATHRI N, MVJCE EXTERNAL GUIDE: MUBASSAR UTOZ, SENIOR SOFTWARE ENGINEER
Keywords: Multi Protocol Mail Server